Neighbourhood deprivation and child behaviour across childhood and adolescence. (1st April 2020) - Flouri, Eirini; Midouhas, Emily; Francesconi, Marta
Abstract : Children living in deprived areas tend to show greater problem behaviour relative to children in more advantaged areas. We explored the effect of different forms of area deprivation (such as income, education and health) on the development of child problem behaviour (emotional and behavioural problems) from early childhood to middle adolescence. Using data from the Millennium Cohort Study, we modelled trajectories of child problem behaviour depending on the level of deprivation in the neighbourhood, across ages 3 to 14 years, in England ( n = 6, 127). We explored seven types of social, economic and environmental deprivation in small standard areas, using the Index of Multiple Deprivation. Child problem behaviour was measured with the Strengths and Difficulties Questionnaire. Most types of deprivation were moderately predictive of child problem behaviour at around age eight (where we set the intercept), when explored in separate models, even after adjustments to reduce area selection bias. However, they were not related to longitudinal changes in problem behaviour. Socio-economic aspects of area deprivation – education, income and employment – were most consistently related to child problem behaviour – and were robust to adjustments for other domains of area deprivation including crime and living environment.